Non-contact Radar Vital Sign Extraction Technology Based on Improved SSSC-EEMD - Wang, Xuejiao; Wen, Liang; Li, Hang; Li, Yan (2024 9th Asia Conference on Power and Electrical Engineering (ACPEE), 2024)
Aiming at the problems of weak signals detection difficulty and signal aliasing of vitals in through-wall radar target vitals detection, this paper addresses the challenges in detecting weak vital signs and signal overlapping in through-wall radar life detection. It introduces a novel ultra-wideband radar life detection algorithm that integrates Soft Sifting Stopping Criterion-based Ensemble Empirical Mode Decomposition (SSSC-EEMD) with a wavelet threshold algorithm. The validation results, based on real-world data, indicate that this algorithm can rapidly and accurately detect human vital signs through walls, outperforming traditional vital sign detection methods. The reconstructed vital signs signals align more closely with actual conditions, showcasing its effectiveness and suitability in resolving the issue of signal overlapping for through-wall vital sign detection.